The Analysis of Dynamic Changes and Prognosis of Posner–Schlossman Syndrome with Cytomegalovirus Infection and Antiviral Therapy - Qilian Sheng; Ruyi Zhai; Xintong Fan; Xiangmei Kong (Journal of Ophthalmology)
Purpose. To analyze how keratic precipitate (KP) morphology changes during Posner–Schlossman syndrome (PSS) prognosis and raise medication suggestions on 2% ganciclovir eye drops. Materials and Methods. Clinical retrospective cohort study in the Eye & ENT Hospital of Fudan University, Shanghai, China. The attacked eyes of 98 eligible subjects diagnosed unilateral PSS were enrolled between 2016 and 2019. All patients were treated with intraocular pressure-lowering drugs and anti-inflammatory steroids. 2% ganciclovir eye drops were given to cytomegalovirus (CMV) immunoglobulin G (IgG) correction ratio positive patients. Frequent follow-ups and examinations were performed. KP morphology was focused and categorized into coin-shaped, mutton-fat, and pigmented. Medical histories were noted. Multidimensional analysis was given. Results. Totally 47 patients in 98 achieved all-KP disappearance. Mean treatment time was (5.13 ± 3.66) weeks. Total KP disappearance was negatively correlated with mutton-fat and pigmented KPs at the first visit (P=0.020, P=0.007) and treatment time was also longer (P=0.018, P=0.014). Mean cumulative steroids dosage for 47 subjects was (159.66 ± 161.84) drops. CMV IgG correction ratio positive patients had smaller corneal endothelial cell density (P<0.005) and larger cup-to-disc ratio (P=0.017) than negative subjects. Cumulative steroid treatment time was longer in the CMV-positive group, and overall dosage was also larger. However, due to 2% ganciclovir eye drops, daily steroid dosage was lower in the CMV-positive group. Conclusions. The disappearance of mutton-fat and pigmented KPs needed longer treatment time. Paired aqueous humor and serum CMV IgG tests were recommended in PSS patients with coin-shaped KPs. 2% ganciclovir eye drops improved prognosis; and steroids dosage reduced significantly.